Patient-centered prescription opioid tapering in community outpatients with chronic pain: 2- to 3-year follow-up in a subset of patients. (17th September 2020) - Ziadni, Maisa; Chen, Abby L.; Krishnamurthy, Parthasarathy; Flood, Pamela; Stieg, Richard L.; Darnall, Beth D.
Abstract : Study findings reveal continued opioid reduction and enduring pain stability for a substantial fraction of patients, 2 to 3 years after a patient-centered voluntary opioid tapering program. Abstract: Objective: We previously reported promising results for a 4-month patient-centered voluntary opioid tapering study. Key questions remain about the durability of effects and possible risks after opioid reduction. We provide the longest follow-up data to date for prospective opioid tapering: 2- to 3-year follow-up for pain intensity and daily opioid use in a subset of patients from our original 4-month opioid tapering study. Methods: Twenty-three patients (44% of original sample) responded to contact attempts through telephone and reported their average pain intensity and current opioid use. Opioid doses were converted to morphine equivalent daily dose (MEDD). Data were analyzed within a repeated-measures model where time (baseline, 4 months, and 2–3 years) was the within-subject factor. Results: Among reachable patients, the effect of time on change in MEDD from baseline to 4 months to 2 to 3 years was significant. Since baseline, 20 (95%) of the current sample reduced MEDD, and 15 (71%) further reduced MEDD at 2- to 3-year follow-up. There was no effect of time on change in pain intensity from baseline to 4 months to 2 to 3 years. Since baseline, 11 (52%) of the current sample reported pain reduction, and 12 (57%) reported reduced pain from the 4-month follow-up to the 2- to 3-year follow-up. Five (24%) reported increased pain intensity. Conclusion: Study findings reveal continued MEDD reduction and enduring pain stability 2 to 3 years after a patient-centered voluntary opioid tapering program for a substantial fraction of patients. Notably, we were not able to verify current opioid use through medical records and were limited by self-report.